“Will You Buy It If They Recommend It?” Exploring the Antecedents of Intention to Purchase Podcaster-Endorsed Items - Huang, Yi-Ting; Gong, An-Di (Journal of theoretical and applied electronic commerce research, 2024)
The diverse content of and ease of listening to podcasts have made podcasts popular, particularly during the COVID-19 pandemic. Advertisers have begun to recognize their marketing potential and are now hiring podcasters to recommend their products. This study sought to determine the factors influencing podcast commitment, parasocial interaction (PSI), and the intention to purchase podcaster-endorsed items. It was conducted in Taiwan with a sample size of 578 participants and an online questionnaire. Structural equation modeling and mediation analysis were applied to the collected data from the perspective of uses and gratifications theory. We found that podcast commitment is positively related to edutainment, storytelling transportation, and social engagement. Social engagement is positively related to PSI, while storytelling transportation has a negative relationship with PSI. Additionally, there is a strong positive correlation between podcast commitment and PSI and both factors positively influence the intention to purchase podcaster-endorsed items. PSI also significantly moderates the positive relationship between podcast commitment and the intent to buy podcaster-endorsed items.